Representasi Kolonial pada Bangunan Istana Bogor - Durrotun Nafisah; Ashif Alfarizi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
This study examines how colonial power is articulated through the form, spatial layout, and symbolism of Bogor Palace, and how post-independence transformations in function and discourse shape its new identity. As a colonial architectural legacy, Bogor Palace holds historical significance and reflects power dynamics, cultural representation, and spatial acculturation in both colonial and postcolonial contexts. The research highlights the importance of reassessing colonial architecture as a medium for representing power and ideology, especially in buildings that remain national symbols. Using a qualitative approach with literature review and visual analysis, the study applies Michel Foucault’s theory of power and discourse to reveal embedded power structures, and Erwin Panofsky’s iconography and iconology to decode visual symbols and meanings. Findings show that the neoclassical European style of the palace reflects colonial dominance, yet its adaptation through local materials, construction techniques, and climate-responsive elements indicates a complex process of acculturation. Initially marginal, local culture becomes integrated into the building’s design. After independence, the palace was resemanticized from a colonial icon to a national emblem, illustrating a shift in identity and power narratives. Today, restoration efforts not only preserve its historical value but also reaffirm role as a dynamic cultural space shaping Indonesia’s collective memory.